Potential Prophylactic and Therapeutic Effects of Respiratory Physiotherapy for COVID-19: Respiratory Physiotherapy for COVID-19 - Shakerian, Narges; Mofateh, Razieh; Saghazadeh, Amene; Rezaei, Niloofar; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2020)
New coronavirus disease 2019 (COVID-19) has succeeded in surprising the world with infecting more than 12 million people and claiming 560,000 lives in only six months. COVID-19 is associated with a spectrum of respiratory symptoms, especially dyspnea. Patients who progress to severe or critical condition display peripheral and posterior lung lesions bilaterally. These patients require admission to the intensive care unit (ICU); therefore, they are prone to ICU-related complications during disease and after recovery. Respiratory physiotherapy techniques, in particular, active techniques, might help the improvement of airway clearance and lung capacity in addition to the reduction of breathing effort during the active disease. In parallel, it might lead to the prevention of disabilities, resulting from infection and extended hospitalization in patients who recovered from COVID-19. This supports physiotherapy both as a prophylactic and therapeutic strategy for COVID-19.